Systemic Relapse in a Young Adult Patient with Primary CNS Diffuse Large B-Cell Lymphoma - Adam Khorasanchi; Zachary Benson; Misty Hall; Nelya Ebadirad; Mohammad H. Gharavi; Patrick Willard; Miranda Chimzar; John McKay; Gary Simmons; Victor Yazbeck (Case Reports in Hematology)
Primary central nervous system diffuse large B-cell lymphoma (PCNS-DLBCL) is a rare form of non-Hodgkin’s lymphoma, characterized by an aggressive disease course. While CNS relapse is common, systemic relapse is rare with no consensus on optimal treatment. This paper presents an unusual case of advanced PCNS-DLBCL with systemic relapse, including adrenal gland involvement. A review of the existing literature and a discussion on the management of systemic relapse in PCNS-DLBCL is also provided.